Evolutionary origins of taro (Colocasia esculenta) in Southeast Asia. Issue 23 (2nd November 2020) - Ahmed, Ibrar; Lockhart, Peter J.; Agoo, Esperanza M. G.; Naing, Kyaw W.; Nguyen, Dzu V.; Medhi, Dilip K.; Matthews, Peter J.
Abstract: As an ancient clonal root and leaf crop, taro ( Colocasia esculenta, Araceae) is highly polymorphic with uncertain genetic and geographic origins. We explored chloroplast DNA diversity in cultivated and wild taros, and closely related wild taxa, and found cultivated taro to be polyphyletic, with tropical and temperate clades that appear to originate in Southeast Asia sensu lato. A third clade was found exclusively in wild populations from Southeast Asia to Australia and Papua New Guinea. Our findings do not support the hypothesis of taro domestication in Papua New Guinea, despite archaeological evidence for early use or cultivation there, and the presence of apparently natural wild populations in the region (Australia and Papua New Guinea). Abstract : As an ancient clonal root and leaf crop, taro ( Colocasia esculenta, Araceae) is highly polymorphic with uncertain genetic and geographic origins. We explored chloroplast DNA variation in wild and cultivated taros and other Colocasia species and found cultivated taro to be polyphyletic, with tropical and temperate clades originating in Southeast Asia. A third clade was found exclusively in wild populations from Southeast Asia to Australia and Papua New Guinea.